Early Muslim Scholars’ Conceptions of Character Development and Contemporary Applications in Mental Health and Well-Being - YÜCESOY, ZEYNEP BETÜL (My University, 2024)
Well-being, as a comprehensive phenomenon related to an individual’s emotional response and life satisfaction, has a vital importance for human beings today. Contemporary perspectives, such as the domain of positive psychology, have shifted from a pathology-oriented perception of well-being and have made efforts to include psychological and spiritual aspects in the picture. The aim of these modern approaches is to activate mechanisms of change and build positive qualities within a person. Similarly, the Islamic tradition has long emphasized the importance of physical, psychological, emotional, and spiritual well-being, with the spiritual dimension at the center of the purpose of personal development. Both modern psychological and Islamic theological perspectives consider character development as essential for increasing well-being. While modern psychology uses character development only as a tool to achieve self-actualization, an Islamic perspective includes, within the concept of self-actualization, the notions and objectives of purification from the evils of the world and the self and attaining the pleasure of God. Islamic scholars in the classical period emphasized the importance of keeping a balance between good and bad character traits within the conception of human well-being. This chapter will discuss the mechanisms and approaches to character development suggested by early Muslim scholars, such as Abu Zayd al-Balkhi (9th century), Abu Hamid al-Ghazali (112th1th century), Al-Razi (13th9th century), and Birgivi (16th16th century), as well as discuss possible contemporary applications in the light of modern psychological studies. It will put forth strategies for Islamically informed character development and their potential for implementation within Islamically-integrated psychotherapy and well-being counseling within contemporary contexts.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Klinik Psikolojisi; Sosyoloji; Sağlık Bilimleri; Social Sciences and Humanities; Psychology; Clinical Psychology; Sociology; Health Sciences; Klinik Tıp (Med); Temel Bilimler (Sci); Sosyal Bilimler (Soc); Psikiyatri; Sosyal Bilimler Genel; Psikoloji Klinik; Kamu Çevre Ve İş Sağlığı; Clinical Medicine (Med); Natural Sciences (Sci); Social Sciences (Soc); Psychiatry; Social Sciences General; Psychology Clinical; Public Environmental & Occupational Health; Sağlık (sosyal bilimler); Sosyal Bilimler ve Beşeri Bilimler; Klinik Psikoloji; Psikiyatri ve Ruh Sağlığı; Health (social science); Social Sciences & Humanities; Psychiatry and Mental Health